Diversity of photoperiodic responses in oats - I. G. Loskutov; V. A. Koshkin; I. I. Matvienko; E. V. Blinova; I. A. Kosareva (Вавиловский журнал генетики и селекции, 2019)
The article presents the results of an evaluation of the earliness and photoperiodic response (PPR) in the long-day oat accessions  of various geographic origin. The material for this study were 139 oat accessions  from the global collection of plant genetic resources  maintained by the Vavilov Institute (VIR), which included  landraces, breeding cultivars, and lines. In addition,  the donors  of low sensitivity to photoperiod developed at VIR were tested. A preliminary field study of the oat collection for early maturity and growing plants in the vegetation experiment was carried out according to the VIR Guidelines. The early accessions from VIR’s oat collection identified in the field showed a great diversity of their photoperiodic responses during the vegetation experiment in a photoperiod facility. By origin, most of the accessions described in the vegetation experiment as earliness  and weakly responsive to photoperiod were from Brazil (66 %); others from the USA, Portugal, Turkey, Colombia and Australia. Most of the Russian cultivars studied (77 %) were sensitive to a short  photoperiod. Among donors  with different  photoperiodic responses, Skorospely 1 and  Skorospely 2 were weakly responsive to photoperiod, while Srednespely 1 and  Srednespely 2 showed medium  responses. Many years of field studies  and vegetation experiments with the  oat genetic diversity from the VIR global collection  have resulted in identifying genotypes characterized by earliness and weak photoperiodic responses. These accessions  are of special value for breeders and currently being used to develop new early and productive oat cultivars.